Electrical Characterization of Silicon-on-Insulator Materials and Devices - Cristoloveanu, Sorin; Li, Sheng S. (The Springer International Series in Engineering and Computer Science, Electronic Materials: Science and Technology, 1995)
Silicon on Insulator is more than a technology, more than a job, and more than a venture in microelectronics; it is something different and refreshing in device physics. This book recalls the activity and enthu siasm of our SOl groups. Many contributing students have since then disappeared from the SOl horizon. Some of them believed that SOl was the great love of their scientific lives; others just considered SOl as a fantastic LEGO game for adults. We thank them all for kindly letting us imagine that we were guiding them. This book was very necessary to many people. SOl engineers will certainly be happy: indeed, if the performance of their SOl components is not always outstanding, they can now safely incriminate the relations given in the book rather than their process. Martine, Gunter, and Y. S. Chang can contemplate at last the amount of work they did with the figures. Our SOl accomplices already know how much we borrowed from their expertise and would find it indecent to have their detailed contri butions listed. Jean-Pierre and Dimitris incited the book, while sharing their experience in the reliability of floating bodies. Our families and friends now realize the SOl capability of dielectrically isolating us for about two years in a BOX. Our kids encouraged us to start writing. Our wives definitely gave us the courage to stop writing. They had a hard time fighting the symptoms of a rapidly developing SOl allergy